ERP system implementation in Latvian manufacturing and construction company - Tambovcevs, Andrejs (Technological and Economic Development of Economy, 2012)
The enterprise resource planning (ERP) software market has been growing at a very fast pace over the last few years and has been predicted to keep growing rapidly in the long term. ERP systems have the potential to integrate seamlessly organizational processes using common shared information and data flows. Enterprises recently tend to implement their new enterprise information systems like ERP system in order to gain their competitive advantages and bring up their business efficiency, but the efficiency gained from this new implementation is not quite clear and is difficult to be identified. This paper presents a case study of ERP systems implementation in international construction materials procurement and purchasing company in Latvia. Specifically, this paper briefly described the business processes involved in the manufacturing and construction company and illustrated how ERP systems could be implemented and the efficiency of management system consequently enhanced. For an international company, the headquarters’ successful experience can provide a guideline to assist the local office to implement new system effectively and efficiently. ERP information system supports manufacturing process and construction object related information. This paper also argues that ERP systems are an increasingly important source of organizational change with major implications for the organization and management of work.